Review Essay: The Literature of the Sages – A Re-visioning - Doering, Lutz (NTT, 2024)
This essay reviews the 2022 volume, The Literature of the Sages: A Revisioning, edited by Christine Hayes in the series Compendia Rerum Iudaicarum ad Novum Testamentum (CRINT).